Sputum proteomic signature of gastro-oesophageal reflux in patients with severe asthma. (April 2019) - Tariq, K.; Schofield, J.P.R.; Nicholas, B.L.; Burg, D.; Brandsma, J.; Bansal, A.T.; Wilson, S.J.; Lutter, R.; Fowler, S.J.; Bakke,; Caruso, M.; Dahlen, B.; et al.
Abstract: Gastro-oesophageal reflux disease (GORD) has long been associated with poor asthma control without an established cause-effect relationship. 610 asthmatics (421 severe/88 mild-moderate) and 101 healthy controls were assessed clinically and a subset of 154 severe asthmatics underwent proteomic analysis of induced sputum using untargeted mass spectrometry, LC-IMS-MS E . Univariate and multiple logistic regression analyses (MLR) were conducted to identify proteins associated with GORD in this cohort. When compared to mild/moderate asthmatics and healthy individuals, respectively, GORD was three- and ten-fold more prevalent in severe asthmatics and was associated with increased asthma symptoms and oral corticosteroid use, poorer quality of life, depression/anxiety, obesity and symptoms of sino-nasal disease. Comparison of sputum proteomes in severe asthmatics with and without active GORD showed five differentially abundant proteins with described roles in anti-microbial defences, systemic inflammation and epithelial integrity. Three of these were associated with active GORD by multiple linear regression analysis: Ig lambda variable 1–47 (p = 0·017) and plasma protease C1 inhibitor (p = 0·043), both in lower concentrations, and lipocalin-1 (p = 0·034) in higher concentrations in active GORD. This study provides evidence which suggests that reflux can cause subtle perturbation of proteins detectable in the airways lining fluid and that severe asthmatics with GORD may represent a distinct phenotype of asthma. Highlights: 5 proteins different in severe asthmatics with GORD. Ig lambda variable 1–47 was associated with active GORD in severe asthma. Lipocalin-1 was associated with active GORD in severe asthma. Plasma protease C1 inhibitor was associated with active GORD in severe asthma.